Sustainable livelihood among aquaculture entrepreneurs: the case of Cambodian migrants in Malaysia - Md. Yassin, Sulaiman; Mohamed Shaffril, Hayrol Azril; Othman, Mohd Shahwahid (Medwell Journals, 2013)
This study attempts to discover the sustainable livelihood among the Cambodian migrants who operate the aquaculture industry in Pekan, Pahang. This study is qualitative in nature, based on a focus group discussion conducted among selected Cambodian migrants in Pulau Keladi Baru village in Pekan. The questions included within the interview protocol were largely based on the Pentagon developed by the department for international development. The Pentagon is a framework for sustainable livelihood based on five main capitals, namely human capital, social capital, financial capital, natural capital and physical capital. The data obtained were later transcribed verbatim and analysed using thematic analysis.